Pengaruh Teknik Relaksasi Pernafasan Dalam terhadap Perilaku Marah Pasien Skizofrenia di UPTD RSJ Provinsi Bali - Desak Made Ari Dwi Jayanti; I Wayan Budianto; I Gusti Ayu Putu Satya Laksmi (LPPM STIKES Guna Bangsa, 2022)
Schizophrenia is a disease that affects the brain, causing strange thoughts, perceptions, emotions, movements and behaviors, one of which appears violent behavior with the most prominent symptom being angry behavior. Anger needs to be prevented from becoming maladaptive, because maladaptive behavior will lead to violent behavior that can harm oneself, others and the environment. Control the patient's risk of violent behavior, including angry behavior by relaxing deep breaths. This study aims to determine the effect of deep breathing relaxation techniques on the angry behavior of schizophrenia patients. The research design used one group pre-test-posttest design. The sample in this study were schizophrenia patients with a risk of violent behavior, totaling 20 people. The sampling technique used purposive sampling, data analysis using the Wilcoxon Sign Rank Test measuring instrument using an angry behavior assessment observation sheet. The results showed that the angry behavior of schizophrenia patients before being given deep breathing relaxation techniques was in the medium category 70%, severe 30%, and after being given deep breathing relaxation techniques the results were 60% mild, 35% moderate, 5% severe. The results of the analysis obtained a value of p = 0.000 (p<0.05), which means that there is an effect of deep breathing relaxation techniques on the angry behavior of schizophrenia patients. Deep breathing relaxation techniques given with the right intensity and rhythm are very good for helping the process of controlling violent behavior. It is recommended to the mental hospital to apply deep breathing relaxation to control angry behavior.